Are young refugees more likely to enter training places with vacancy problems? : comparisons between immigrant youths in Germany - Christ, Alexander [Verfasser]; Winkler, Oliver [Verfasser] (My University, 2026)
"In Germany, young refugees participate in vocational education and training (VET) at significantly lower rates than non-migrants and migrants without a refugee background. At the same time, the German training market is increasingly characterized by shortages of applicants in specific training occupations, resulting in a growing number of unfilled training places. During the refugee inflow of 2015 and 2016, policymakers, employers, and researchers emphasized the potential of vocational training to promote refugees' labor market integration while simultaneously alleviating recruitment problems in shortage occupations. Entering VET may also improve refugees' prospects for remaining in Germany, particularly for those with insecure residence status. Against this background, this study examines whether young refugees are disproportionately likely to enter training occupations with vacancy problems and whether legal insecurity further shapes these transitions." (author's abstract ; BIBB-Doku)
Keywords: P 1.5 Migranten; G 1.3.1.1 Ausbildungsstellenmarkt; 370; 330; Ausbildungsstellenmarkt; Ausbildungsstellenmarkt Ausbildungsstellenbewerber; Flüchtling; Migrant; Arbeitsmarkt; Berufliche Integration; Mangelberuf; BA/BIBB Bewerberbefragung